A nickel-cobalt-manganese ternary precursor and its preparation method, and its application in lithium-ion batteries.

By controlling precursor particle growth using hard microspheres, the method addresses the anisotropic volume changes in nickel-cobalt-manganese ternary cathode materials, enhancing the tap density and uniformity of the precursor, resulting in a lithium-ion battery with improved rate performance and mechanical stability.

CN115849464BActive Publication Date: 2024-12-27ZHEJIANG HUAYOU COBALT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211649416.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2024-12-27
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Existing nickel-cobalt-manganese ternary cathode materials face issues with anisotropic volume changes during charging, leading to microcracks and poor mechanical stability due to uncontrollable particle size and morphology, which affects the performance of lithium-ion batteries.

Method used

A method involving the use of hard microspheres during the coprecipitation reaction to control the growth of precursor particles along the c-axis, forming a lamellar morphology, which enhances tap density and uniformity, resulting in a single-crystal positive electrode material with improved dispersibility and reduced agglomeration.

Benefits of technology

The method produces a nickel-cobalt-manganese ternary precursor with uniform particle size and high tap density, leading to a lithium-ion battery with excellent rate performance and improved mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115849464B_ABST
    Figure CN115849464B_ABST
Patent Text Reader

Abstract

The present application provides a nickel-cobalt-manganese ternary precursor and its preparation method and lithium-ion battery, which relate to the field of power batteries. The nickel-cobalt-manganese ternary precursor is composed of nickel-cobalt-manganese hydroxide, which is granular in appearance, and the main body of the particle is composed of stacked sheets grown along the c-axis. The preparation method of the nickel-cobalt-manganese ternary precursor is to add hard microspheres to the chemical coprecipitation reaction. The hard microspheres are non-metallic microspheres and are insoluble in strong alkali and hot water. The hard microspheres are spherical, with an average particle size of 300 to 800 μm and a density greater than 1.00 g / cm 3 , less than 2.00g / cm 3 The nickel-cobalt-manganese ternary precursor is easy to produce industrially, has uniform particle size, high tap density, and the prepared ternary positive electrode has excellent rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of power batteries, and more specifically, to a nickel-cobalt-manganese ternary precursor and a preparation method thereof and a lithium-ion battery. Background Art

[0002] At present, nickel-cobalt-manganese ternary cathode materials occupy a huge market share in the field of power batteries due to their high energy density. However, during the charging process of ternary cathode materials, as lithium ions are released, the internal stress accumulation of the material will cause anisotropic volume changes in the particles and form microcracks, resulting in a decrease in the stability of the material. Preparing ternary cathode materials into single-crystal-like particles can greatly improve the mechanical strength and compaction density of the material. After multiple cycles, the pulverization of the primary particle interface can still be avoided, thereby improving the material performance. The properties of the ternary precursor have a crucial influence on the performance of the cathode material. The particle size and morphology of the precursor will directly affect the morphology of the cathode material. The synthesis of single-crystal cathode materials usually uses small-particle precursors because small-particle precursors have higher solid-phase reaction activity and are easier to grow into single-crystal morphology. However, due to the short growth time of small-particle precursors, the morphology and particle size are uncontrollable; and due to the small particle size, the particles are easy to agglomerate, resulting in poor morphology uniformity, affecting the tap density and physical and chemical properties of the material.

[0003] The reported patented technology improves the dispersion and sphericity of the precursor by controlling the ventilation position of the protective gas, using bubbles to inhibit the collision and agglomeration of the precursor particles, and increasing the turbulent diffusion in the dead zone of the circulation. However, large-flow ventilation will cause serious ammonia volatilization, resulting in uncontrollable ammonia values, affecting the control of process parameters, and the effect of bubbles in inhibiting agglomeration is limited, and the improvement effect of material agglomeration is small. Summary of the invention

[0004] The purpose of the present application is to provide a nickel-cobalt-manganese ternary precursor and a preparation method thereof and a lithium-ion battery. The nickel-cobalt-manganese ternary precursor is easy to industrialize and produce, has a uniform particle size, and a high tap density. The prepared ternary positive electrode has excellent rate performance.

[0005] In a first aspect, the present application provides a nickel-cobalt-manganese ternary precursor, which is composed of nickel-cobalt-manganese hydroxide, has a granular appearance, and the particle body is composed of stacked sheets grown along the c-axis.

[0006] In the above technical scheme, the nickel-cobalt-manganese ternary precursor has a lamellar morphology rather than a conventional coil-shaped morphology, which can improve the tap density of the material; and the stacked growth of the precursor particles along the c-axis is beneficial to the diffusion of lithium during high-temperature calcination to prepare the positive electrode, and promotes the lithiation reaction. The lithium-ion battery formed by the single crystal positive electrode material prepared with the ternary precursor has excellent rate performance.

[0007] In one possible implementation, the average particle size of the particles is 2.5 to 3.2 μm, and the tap density is 1.75 to 2.05 g / cm 3 .

[0008] In the above technical solution, the particle size distribution is uniform and the interior is very dense. The particles of the single crystal positive electrode material prepared using the precursor have good dispersion and uniform particle size distribution.

[0009] In a second aspect, the present application provides a method for preparing the nickel-cobalt-manganese ternary precursor provided in the first aspect, comprising:

[0010] The hard microspheres are mixed with water to obtain a base liquid. The hard microspheres are non-metallic microspheres with a Shore hardness of 50 to 90 HD and are insoluble in strong alkaline solutions and hot water at 50 to 80 ° C. The hard microspheres are spherical in shape, with an average particle size of 300 to 800 μm and a density greater than 1.00 g / cm 3 , less than 2.00g / cm 3 ;

[0011] Adding the nickel-cobalt-manganese mixed salt solution, the precipitant and the complexing agent into the bottom liquid in parallel, and carrying out a chemical coprecipitation reaction under stirring conditions;

[0012] The reacted material is sieved to remove hard microspheres with large particle sizes, and the remaining solid material is washed and dried.

[0013] In the above technical scheme, hard microspheres of 100 micrometers are introduced into the co-precipitation reaction system before the reaction starts. During the reaction, the precursor first nucleates to form primary particles. As the reaction proceeds, the primary particles grow and agglomerate into secondary particles along the crystal planes. With the introduction of hard microspheres of 100 micrometers, the microspheres will continuously collide with the precursor particles. The collision force competes with the growth force of the precursor along the crystal plane. The growth force of the precursor along the c-axis is the strongest, which is stronger than the collision force, while the growth force along other crystal planes is suppressed, eventually forming a lamellar morphology stacked along the c-axis.

[0014] The continuous collision of the 100-micron hard microspheres with the precursor particles also solves the problem of easy agglomeration of particles due to low solid content of the system in the initial stage of the reaction and insufficient collision force between particles: through stirring, the hard microspheres and the precursor particles are constantly collided, and the collision between the microspheres and the particles allows the crystal nuclei formed in the nucleation stage to be evenly dispersed in the solution, which can effectively slow down the growth rate of the particles and prepare a small-particle ternary precursor with high tap density and uniform dispersion, that is, to improve the dispersibility of the primary particles of the precursor and avoid the agglomeration of particles caused by the small particle size and large particle surface energy of the primary particles. It is precisely because this technology solves the agglomeration phenomenon of small-particle ternary precursors that the use of the well-dispersed precursor particles can avoid adhesion between the positive electrode particles when sintering the single crystal positive electrode, thereby obtaining a single crystal positive electrode material with uniform particle size distribution and high dispersion.

[0015] Moreover, the density of the introduced hard microspheres is close to that of the precursor particles, and they can be effectively mixed and collided with the precursor, avoiding the phenomenon that the hard microspheres and the precursor are difficult to mix, resulting in a significant reduction in the collision strength between the particles; the particle size of the hard microspheres is much larger than that of the precursor particles, and they can be easily separated from the system by screening without adding additional post-processing costs.

[0016] In a possible implementation, the volume proportion of the hard microspheres in the base liquid is 25% to 75%.

[0017] In the above technical scheme, when the volume proportion of hard microspheres in the base liquid is too small, the collision intensity is insufficient and it is difficult to form a lamellar morphology. When the volume proportion of hard microspheres in the base liquid is too large, the solid content in the reaction system is too high and the collision intensity is too large. The material cannot precipitate and grow on the existing precursor particles. In addition, a large proportion of microspheres will result in low effective solid content and reduced production capacity.

[0018] In a possible implementation, during the reaction process, the pH of the reaction system is controlled to be 10.5-11.4, and the ammonia concentration is controlled to be 2-20 g / L.

[0019] In the above technical solution, the pH and ammonia concentration need to be controlled in an appropriate range. The pH and ammonia concentration directly affect the nucleation and growth of the precursor particles. Too large or too small will affect the growth rate of the precursor, thereby affecting the tap density and morphology of the precursor.

[0020] In a possible implementation, the reaction atmosphere is an inert gas or air or a mixture of the two, the reaction temperature is 45 to 60° C., and the stirring speed is 800 to 1500 rpm / min.

[0021] In the above technical solution, the precursor material will be partially oxidized under air atmosphere. The oxidation effect can inhibit the stacking growth of the precursor along the c-axis to a certain extent. The stacking thickness and compactness of the precursor can be regulated by controlling the amount of air introduced.

[0022] In a possible implementation, the pH of the base liquid is first adjusted to 10.5-11.4, the ammonia concentration is 2-20 g / L, and the temperature is 45-60° C.; then the nickel-cobalt-manganese mixed salt solution, the precipitant, and the complexing agent are added to the base liquid in parallel.

[0023] In a possible implementation, when the particle size of the precursor generated by the reaction reaches 2.5 μm or more, the feeding is stopped, and the stirring and aging are continued for 1 to 2 hours;

[0024] And / or, a sieve is used for screening, and the material on the sieve is hard microspheres.

[0025] In the above technical solution, the hard microspheres are separated from the precursor particles according to the difference in particle size between the two, and the hard microspheres can be recycled and reused after being rinsed clean.

[0026] In a possible implementation, a nickel-cobalt-manganese mixed salt solution is prepared using NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O, wherein the metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 2 to 3 mol / L;

[0027] And / or, the precipitant is a 6-10 mol / L NaOH aqueous solution, and the complexing agent is a 10%-28% by mass ammonia water.

[0028] In a third aspect, the present application provides a lithium-ion battery comprising a single crystal positive electrode material prepared from the nickel-cobalt-manganese ternary precursor provided in the first aspect.

[0029] In the above technical solution, the lithium-ion battery has excellent rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 A schematic diagram of the crystal structure of the precursor of the present application;

[0032] Figure 2 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Example 6 (magnification is 1k);

[0033] Figure 3 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Example 6 (magnification is 5k);

[0034] Figure 4 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Example 6 (magnification is 10k);

[0035] Figure 5 This is a scanning electron microscope image of a slice of the nickel-cobalt-manganese ternary precursor obtained in Example 6 (magnification is 5k);

[0036] Figure 6 This is a scanning electron microscope image of a slice of the nickel-cobalt-manganese ternary precursor obtained in Example 6 (magnification is 10k);

[0037] Figure 7 This is the X-ray diffraction pattern of the nickel-cobalt-manganese ternary precursor obtained in Example 6;

[0038] Figure 8 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Comparative Example 1 (magnification is 1k);

[0039] Fig. 9 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Comparative Example 1 (magnification is 5k);

[0040] Fig.10 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Comparative Example 1 (magnification is 10k);

[0041] Fig.11 This is a scanning electron microscope image of the nickel-cobalt-manganese ternary precursor obtained in Comparative Example 2;

[0042] Fig.12 This is the X-ray diffraction pattern of the nickel-cobalt-manganese ternary precursor obtained in Comparative Example 1;

[0043] Fig.13 This is a scanning electron microscope image of the single crystal positive electrode material obtained by sintering the nickel-cobalt-manganese ternary precursor obtained in Example 6. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0045] The nickel-cobalt-manganese ternary precursor and its preparation method and lithium-ion battery of the present application are described in detail below.

[0046] The present application provides a nickel-cobalt-manganese ternary precursor, which is composed of nickel-cobalt-manganese hydroxide, namely Ni x Co y Mn (1-x-y) (OH)2, x = 0.8 ~ 0.98, y = 0.01 ~ 0.1, the shape is granular, and the particle body is composed of stacked sheets growing along the c-axis; the average particle size of the particles is usually 2.5 ~ 3.2μm, and the tap density is usually 1.75 ~ 2.05g / cm 3 .

[0047] The present application also provides a method for preparing a nickel-cobalt-manganese ternary precursor, which comprises the following steps:

[0048] S1. Mix hard microspheres with water to obtain a base solution. The hard microspheres are non-metallic microspheres and need to meet the following conditions:

[0049] (a) Spherical, average particle size is 300-800 μm.

[0050] (b) Density greater than 1.00 g / cm 3 , less than 2.00g / cm 3 .

[0051] (c) It is insoluble in hot water (aqueous solution at a temperature of 50 to 80°C) and insoluble in strong alkali (alkaline solution with a pH of 11-13, such as aqueous sodium hydroxide solution), ensuring that the introduced hard microspheres have good stability, are insoluble in the reaction system, will not react with the precursor, will not introduce impurities, and will not cause unpredictable effects on the precursor product.

[0052] (d) The Shore hardness is 50-90 HD, and it does not deform after long-term intense stirring, ensuring that the introduced hard microspheres have high hardness, are not easy to deform, and can be recycled and reused.

[0053] Exemplarily, the hard microspheres are cation exchange resin microspheres, polystyrene-divinylbenzene microspheres with high sphericity. The material of the hard microspheres used in this application is not limited thereto. In addition to polystyrene-divinylbenzene, other polymer materials such as polyethylene, polypropylene, and polystyrene may also be used.

[0054] In order to ensure the effect of the hard microspheres in the system, the volume proportion of the hard microspheres in the base liquid is 25% to 75%.

[0055] S2. Add the nickel-cobalt-manganese mixed salt solution, the precipitant and the complexing agent into the bottom liquid in parallel, and carry out a chemical coprecipitation reaction under stirring conditions.

[0056] As an implementation method, NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O are used to prepare a nickel-cobalt-manganese mixed salt solution, in which the metal ion concentration is 2-3 mol / L; the precipitant is a 6-10 mol / L NaOH aqueous solution, and the complexing agent is ammonia water with a mass fraction of 10% to 28%.

[0057] During the reaction, the pH of the reaction system is controlled to be 10.5-11.4, optionally 10.6-11.3, and the ammonia concentration is 2-20 g / L, optionally 9-18 g / L; the reaction atmosphere is an inert gas or air or a mixture of the two, the reaction temperature is 45-60°C, and the stirring speed is 800-1500 rpm / min.

[0058] Before the reaction, the base liquid is usually adjusted to meet the reaction conditions, specifically, the pH of the base liquid is 10.5-11.4, optionally 10.6-11.3, the ammonia concentration is 2-20 g / L, optionally 9-18 g / L, inert gas or air or a mixture of the two is introduced, the temperature is 45-60°C, and the stirring speed is 800-1500 rpm / min; then the nickel-cobalt-manganese mixed salt solution and the precipitant and the complexing agent are added to the base liquid in parallel to start the reaction.

[0059] During the reaction, the materials are continuously fed in parallel. When the liquid level reaches a certain level, the feeding and stirring are stopped. The precursor and hard microspheres generated by the reaction are allowed to settle naturally. After the upper clear liquid is extracted, the feeding and stirring are resumed, and the above process is repeated as needed.

[0060] S3. During the reaction, samples are taken every 1 to 2 hours, and the particle size of the generated precursor is detected by a laser particle size analyzer. When the particle size of the precursor generated by the reaction reaches 2.5 μm or more, the feeding is stopped, and stirring and aging is continued for 1 to 2 hours. During aging, stirring and temperature are maintained. The reacted material is sieved to remove hard microspheres with large particle sizes. A 200-mesh sieve is usually used to sieve the solid material. The material on the sieve is the hard microsphere. The remaining solid material is washed and dried.

[0061] The nickel-cobalt-manganese ternary precursor prepared by the preparation method of the present application is the nickel-cobalt-manganese ternary precursor for which protection is requested in the present application, and its particles have a stacked morphology.

[0062] Figure 1The crystal structure of the precursor is displayed. The precursor has a hexagonal layered structure, a high hydroxide ion concentration on the (001) plane, and a high surface energy. In the coprecipitation reaction used to form the precursor, the metal ammine complex ions tend to adsorb on the (001) plane and combine with the hydroxide ions on the (001) plane to form a hydroxide precipitate. Therefore, the growth force of the precursor along the c-axis perpendicular to the (001) plane is the strongest, stronger than the collision force, while the growth force along other crystal planes is suppressed, ultimately forming a stacked morphology along the c-axis.

[0063] In the lithium battery industry chain, the final performance of the positive electrode material will inherit the morphological and structural characteristics of its precursor. The quality of the precursor (morphology, particle size, particle size distribution, specific surface area, impurity content, tap density, etc.) directly determines the physical and chemical indicators of the positive electrode sintered product. Therefore, this application introduces hard microspheres when preparing the precursor, which is conducive to the synthesis of high-density, uniform-particle-size single-crystalline positive electrode materials.

[0064] The present application also provides a lithium-ion battery, which contains a single crystal positive electrode material prepared from the above-mentioned nickel-cobalt-manganese ternary precursor.

[0065] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0066] Example 1

[0067] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0068] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0069] (2) Using a 5L reactor as a reactor, add 1L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 11.30 and the ammonia concentration 9 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the reactor jacket water inlet and water return, control the temperature in the reactor to 50°C, and introduce nitrogen into the reactor as a protective gas.

[0070] (3) Under continuous stirring at a speed of 1500 rpm, the nickel-cobalt-manganese mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 11.30, and the ammonia concentration is 9 g / L.

[0071] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 11.30 and the ammonia concentration to 9 g / L.

[0072] (5) Repeat steps (3) and (4) as needed.

[0073] (6) During the reaction, samples were taken every 2 hours and the particle size of the generated precursor was detected by a laser particle size analyzer. When the particle size of the precipitate generated in the reactor reached about 3 μm, the feed was stopped and stirring and aging was continued for 2 hours.

[0074] (7) filtering the aged material in step (6) with a 200-mesh sieve, the material on the sieve is the cation exchange resin microspheres, which can be recycled after being rinsed clean; filtering the separated precursor product for solid-liquid separation, washing the separated filter cake with a 5% hot sodium hydroxide solution, and then rinsing with hot pure water to obtain a washed filter cake.

[0075] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor. After testing, the nickel-cobalt-manganese ternary precursor is nickel-cobalt-manganese hydroxide.

[0076] Example 2

[0077] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0078] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0079] (2) Using a 5L reactor as a reactor, add 1L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 10.60 and the ammonia concentration 9 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the reactor jacket water inlet and water return, control the temperature in the reactor to 50°C, and introduce nitrogen into the reactor as a protective gas.

[0080] (3) Under continuous stirring at a speed of 1500 rpm, the nickel-cobalt-manganese mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 10.60, and the ammonia concentration is 9 g / L.

[0081] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 10.60 and the ammonia concentration to 9 g / L.

[0082] (5) Repeat steps (3) and (4) as needed.

[0083] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0084] (7) filtering the aged material in step (6) with a 200-mesh sieve, the material on the sieve is the cation exchange resin microspheres, which can be recycled after being rinsed clean; filtering the separated precursor product for solid-liquid separation, washing the separated filter cake with a 5% sodium hydroxide solution, and then rinsing with pure water to obtain a washed filter cake.

[0085] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor.

[0086] Example 3

[0087] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0088] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0089] (2) Using a 5L reactor as a reactor, add 1L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 11.30 and the ammonia concentration 18 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the reactor jacket water inlet and water return, control the temperature in the reactor to 50°C, and introduce nitrogen into the reactor as a protective gas.

[0090] (3) Under continuous stirring at a speed of 1500 rpm, the mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the temperature of the reactor is controlled to be 50° C., the pH to be 11.30, and the ammonia concentration to be 18 g / L.

[0091] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 11.30 and the ammonia concentration to 18 g / L.

[0092] (5) Repeat steps (3) and (4) as needed.

[0093] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0094] (7) filtering the aged material in step (6) with a 200-mesh sieve, the material on the sieve is the cation exchange resin microspheres, which can be recycled after being rinsed clean; filtering the separated precursor product for solid-liquid separation, washing the separated filter cake with a 5% sodium hydroxide solution, and then rinsing with pure water to obtain a washed filter cake.

[0095] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor.

[0096] Example 4

[0097] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0098] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0099] (2) Using a 5L reactor as a reactor, add 0.5L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 10.60 and the ammonia concentration 9 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the reactor jacket water inlet and water return, control the temperature in the reactor to 50°C, and introduce nitrogen into the reactor as a protective gas.

[0100] (3) Under continuous stirring at a speed of 1500 rpm, the nickel-cobalt-manganese mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 10.60, and the ammonia concentration is 9 g / L.

[0101] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 10.60 and the ammonia concentration to 9 g / L.

[0102] (5) Repeat steps (3) and (4) as needed.

[0103] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0104] (7) filtering the aged material in step (6) with a 200-mesh sieve, the material on the sieve is the cation exchange resin microspheres, which can be recycled after being rinsed clean; filtering the separated precursor product for solid-liquid separation, washing the separated filter cake with a 5% sodium hydroxide solution, and then rinsing with pure water to obtain a washed filter cake.

[0105] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor.

[0106] Example 5

[0107] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0108] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0109] (2) Using a 5L reactor as a reactor, add 1.5L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 10.60 and the ammonia concentration 9 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the reactor jacket water inlet and water return, control the temperature in the reactor to 50°C, and introduce nitrogen into the reactor as a protective gas.

[0110] (3) Under continuous stirring at a speed of 1500 rpm, the nickel-cobalt-manganese mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 10.60, and the ammonia concentration is 9 g / L.

[0111] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 10.60 and the ammonia concentration to 9 g / L.

[0112] (5) Repeat steps (3) and (4) as needed.

[0113] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0114] (7) filtering the aged material in step (6) with a 200-mesh sieve, the material on the sieve is the cation exchange resin microspheres, which can be recycled after being rinsed clean; filtering the separated precursor product for solid-liquid separation, washing the separated filter cake with a 5% sodium hydroxide solution, and then rinsing with pure water to obtain a washed filter cake.

[0115] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain nickel-cobalt-manganese hydroxide.

[0116] Example 6

[0117] This embodiment provides a nickel-cobalt-manganese ternary precursor, and the preparation method thereof comprises the following steps:

[0118] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0119] (2) Using a 5L reactor as a reactor, add 1L of cation exchange resin microspheres (polystyrene-divinylbenzene microspheres, with a particle size of 580-700 μm and a density of 1.27 g / mL), add pure water until the bottom liquid volume reaches 2L, and then add appropriate amounts of the precipitant and complexing agent prepared in step (1) to make the bottom liquid pH in the reactor 10.60 and the ammonia concentration 9 g / L; start stirring, set the speed to 1500 rpm / min, and at the same time open the water inlet and return water of the reactor jacket, control the temperature in the reactor to 50°C, open the reactor outlet valve, and react in an air atmosphere.

[0120] (3) Under continuous stirring at a speed of 1500 rpm, the nickel-cobalt-manganese mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 10.60, and the ammonia concentration is 9 g / L.

[0121] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 10.60 and the ammonia concentration to 9 g / L.

[0122] (5) Repeat steps (3) and (4) as needed.

[0123] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0124] (7) The aged material in step (6) is filtered through a 200-mesh screen, and the material on the screen is the cation exchange resin microspheres, which can be recycled after being rinsed. The separated precursor product is filtered for solid-liquid separation, and the separated filter cake is first washed with a 5% sodium hydroxide solution and then washed with pure water to obtain a washed filter cake.

[0125] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor.

[0126] Example 7

[0127] This embodiment provides a nickel-cobalt-manganese ternary precursor, and its preparation method is different from that of Example 6 in that the ammonia concentration in this embodiment is 3 g / L.

[0128] Example 8

[0129] This embodiment provides a nickel-cobalt-manganese ternary precursor, and its preparation method is different from that of Example 6 in that: the reaction temperature in this embodiment is 60°C.

[0130] Example 9

[0131] This embodiment provides a nickel-cobalt-manganese ternary precursor, and its preparation method is different from that of Example 6 in that: the rotation speed in this embodiment is 1000 rpm.

[0132] Comparative Example 1

[0133] This comparative example provides a nickel-cobalt-manganese ternary precursor. The preparation method thereof is different from that of Example 2 in that Cation exchange resin microspheres , specifically including the following steps:

[0134] (1) NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were weighed in a molar ratio of 92:4:4 to prepare a nickel-cobalt-manganese mixed salt solution with a metal ion concentration of 2.3 mol / L; 8 mol / L NaOH aqueous solution was prepared as a precipitant and 28% ammonia water as a complexing agent.

[0135] (2) A 5L reactor was used as the reactor, 2L of pure water was added as the bottom liquid, and then an appropriate amount of the precipitant and complexing agent prepared in step (1) was added to make the pH of the bottom liquid in the reactor 10.60 and the ammonia concentration 9g / L. Stirring was started, the speed was set to 1500rpm / min, and the water inlet and return of the reactor jacket were opened at the same time. The temperature in the reactor was controlled to 50°C, and nitrogen was introduced as the protective gas.

[0136] (3) Under continuous stirring at a speed of 1500 rpm, the mixed metal salt solution prepared in step (1), the precipitant and the complexing agent are added to the reactor in parallel for reaction, and the reactor temperature is controlled to be 50° C., the pH is 10.60, and the ammonia concentration is 9 g / L.

[0137] (4) Continue feeding according to step (3). When the liquid level reaches the overflow port of the reactor, stop feeding and turn off stirring. Let the precursor material stand to allow it to settle naturally. Draw out the supernatant, turn on stirring and feeding, and continue the reaction. Control the pH to 10.60 and the ammonia concentration to 9 g / L.

[0138] (5) Repeat steps (3) and (4) as needed.

[0139] (6) When the particle size of the precipitate generated in the reactor reaches about 3 μm, stop feeding and continue stirring and aging for 2 hours.

[0140] (7) The material aged in step (6) is subjected to solid-liquid separation, and the separated filter cake is first washed with a 5% sodium hydroxide solution and then rinsed with pure water to obtain a washed filter cake.

[0141] (8) The filter cake in step (7) is placed in a forced air drying oven and dried at 80° C. for 20 h, and then sieved and demagnetized to obtain a nickel-cobalt-manganese ternary precursor.

[0142] Comparative Example 2

[0143] This comparative example provides a nickel-cobalt-manganese ternary precursor. The main difference between its preparation method and Example 2 is that Different hard microspheres , for specific steps, refer to Example 3 of CN110040790B.

[0144] 1. The performance of the samples prepared in the embodiments and comparative examples was tested, and the results are shown in Table 1.

[0145] Table 1 Preparation process parameters and performance parameters of samples obtained in Examples 1 to 9 and Comparative Examples 1 to 2

[0146]

[0147]

[0148] It can be seen from Examples 1 to 9 that by changing the "volume ratio of microspheres in the base liquid, reaction temperature, stirring speed, pH or ammonia concentration", although the particle size of the obtained samples is not much different, there is still a difference in density. This is because the growth time of the precursor under different preparation process parameters is different, resulting in differences in the final morphology and density of the obtained samples. In particular, the sample obtained in Example 6 has the highest tap density and the best sphericity. It is speculated that this is because the precursor material will undergo partial oxidation in an air atmosphere, and the oxidation effect can inhibit the stacking growth of the precursor along the c-axis to a certain extent. Therefore, the precursor prepared in an air atmosphere has a relatively better sphericity.

[0149] Second, the morphology and structure of the samples obtained in the examples and comparative examples were tested. The microscopic morphology of the sample obtained in Example 6 is as follows: Figure 2 to Figure 4 As shown, the microscopic morphology of the slice is Figure 5-6 The crystal structure is shown in Figure 7 As shown; the microscopic morphology of the sample obtained in Comparative Example 1 is as follows Figure 8 to Figure 10 As shown, the microscopic morphology of the sample obtained in Comparative Example 2 is as follows Fig.11 The crystal structure is shown in Fig.12 shown.

[0150] By comparative analysis, it can be seen that the precursor sample obtained by adding no hard microspheres in comparative example 1 has a coil-like morphology, and some particles will agglomerate and grow into long strips or dumbbells. The precursor particles are uneven in size and have poor particle size uniformity. The hard microspheres added in comparative example 2 and the hard microspheres used in this application have obvious differences in particle size and density, and the final precursor product morphology is still a typical coil-like morphology ( Fig.11 ), which is different from the lamellar precursor prepared in Example 6; the precursor sample prepared in Example 6 has a lamellar morphology, and the interior of the particles is very dense, and the morphologies of the two are significantly different.

[0151] according to Figure 7 and Fig.12 The X-ray diffraction (XRD) results shown in the figure show that the crystal plane orientations of Example 6 and Comparative Example 1 are also significantly different. Figure 7 In the X-ray diffraction pattern of Example 6 shown in FIG. 1 , the peak intensity of the (101) crystal plane is stronger than that of the (001) crystal plane, and Fig.12 The X-ray diffraction pattern of Comparative Example 1 is just the opposite, with the peak intensity of the (001) crystal plane being stronger than that of the (101) crystal plane. Combining the performance parameters of the samples obtained in Examples 1 to 9, it can be seen that after adding hard microspheres to the coprecipitation reaction system, by controlling the amount of hard microspheres added, reaction temperature, stirring speed, pH and ammonia value, the obtained ternary precursor particles are uniformly dispersed, and the primary particles grow along the c-axis in a stacked lamellar morphology, which is significantly different from the coil-type morphology obtained by the conventional method. The lamellar morphology of the precursor sample reduces the gaps between particles and increases the tap density.

[0152] 3. Performance testing of positive electrode materials and lithium-ion batteries.

[0153] The samples prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were respectively used to prepare single crystal positive electrode materials in the following manner:

[0154] The obtained nickel-cobalt-manganese ternary precursor was mixed with lithium hydroxide monohydrate (TM:Li=1:1.05), heated to 500°C and sintered for 2h in an oxygen atmosphere, programmed to 790°C, sintered for 3h, then cooled to 700°C, sintered for 12h, crushed by a jet mill, and sieved through 500 mesh to obtain a single crystal positive electrode material.

[0155] Fig.13 This is a scanning electron microscope image of a single crystal positive electrode material obtained by sintering the nickel-cobalt-manganese ternary precursor prepared in Example 6. Fig.13 It can be seen that the single crystal positive electrode particles prepared using the precursor of the embodiment of the present application have good dispersibility and uniform particle size distribution.

[0156] The above-prepared single crystal positive electrode material, conductive agent (super P) and binder (polyvinylidene fluoride) were mixed evenly in a mass ratio of 93:5:2, and then an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent for stirring to obtain a positive electrode slurry, which was coated on an aluminum foil and dried in a vacuum as a positive electrode sheet. In a glove box, a CR2032 button battery was assembled in the order of a positive electrode shell, a positive electrode sheet, a separator, an electrolyte, a lithium sheet, and a negative electrode shell, and the rate performance of each battery was tested. The results are shown in Table 2.

[0157] Table 2 Rate performance of different batteries

[0158] sample <![CDATA[Rate performance (discharge capacity at 5C / mAh·g -1 )]]> Example 1 C1 185 Example 2 C2 188 Example 3 C3 182 Example 4 C4 183 Example 5 C5 186 Example 6 C6 190 Example 7 C7 183 Example 8 C8 185 Example 9 C9 181 Comparative Example 1 D1 165 Comparative Example 2 D2 /

[0159] As can be seen from Table 2, the single crystal positive electrode prepared by the precursor of the laminated morphology of the embodiment of the present application is more conducive to the transmission of lithium ions than the single crystal positive electrode prepared by the precursor of the coil-shaped morphology of Comparative Example 1, and the discharge capacity is higher at a large rate of 5C, and the corresponding battery has excellent rate performance. Although the precursor of Comparative Example 2 has a high tap density, it is also a conventional coil-shaped morphology. It is speculated that the rate performance of the battery prepared therefrom will be worse than the rate performance of the battery prepared by the precursor of the embodiment of the present application.

[0160] In addition, in the process of preparing the precursor in Comparative Example 2, the hard microspheres are suspended on the surface of the slurry, while the precursor is dispersed in the slurry, which requires a lot of time to wait for the slurry to settle, and the separation effect between the precursor and the hard microspheres is not ideal.

[0161] In summary, the nickel-cobalt-manganese ternary precursor of the present application has uniform particle size and high tap density, and the prepared ternary positive electrode has excellent rate performance.

[0162] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a nickel-cobalt-manganese ternary precursor, characterized in that: include: The hard microspheres are mixed with water to obtain a base liquid, wherein the volume proportion of the hard microspheres in the base liquid is 25% to 75%, the hard microspheres are non-metallic microspheres with a Shore hardness of 50 to 90 HD, and are insoluble in strong alkaline solutions and hot water at 50 to 80° C. The hard microspheres are spherical, have an average particle size of 300 to 800 μm, and a density greater than 1.00 g / cm 3 , less than 2.00g / cm 3 ; First, the pH of the base liquid is adjusted to 10.5-11.4 and the ammonia concentration is 2-20 g / L, and then the nickel-cobalt-manganese mixed salt solution, the precipitant and the complexing agent are added to the base liquid in parallel, and a chemical coprecipitation reaction is carried out under stirring conditions, and the reaction atmosphere is an inert gas or air or a mixture of the two. During the reaction process, the pH of the reaction system is controlled to be 10.5-11.4, the ammonia concentration is 2-20 g / L, the reaction temperature is 45-60° C., and the stirring speed is 800-1500 rpm / min; The reacted material is sieved to remove hard microspheres with large particle sizes, and the remaining solid material is washed and dried.

2. The method for preparing the nickel-cobalt-manganese ternary precursor according to claim 1, characterized in that: First, the temperature of the base liquid is adjusted to 45-60° C.; then, the nickel-cobalt-manganese mixed salt solution, the precipitant and the complexing agent are added to the base liquid in parallel.

3. The method for preparing the nickel-cobalt-manganese ternary precursor according to claim 1, characterized in that: When the particle size of the precursor generated by the reaction reaches 2.5 μm or more, stop feeding and continue stirring and aging for 1 to 2 hours; And / or, a sieve is used for screening, and the material on the sieve is hard microspheres.

4. The method for preparing the nickel-cobalt-manganese ternary precursor according to claim 1, characterized in that: A nickel-cobalt-manganese mixed salt solution is prepared by using NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O, wherein the metal ion concentration in the nickel-cobalt-manganese mixed salt solution is 2-3 mol / L; And / or, the precipitant is a 6-10 mol / L NaOH aqueous solution, and the complexing agent is a 10%-28% by mass ammonia solution.

5. A nickel-cobalt-manganese ternary precursor, characterized in that: The nickel-cobalt-manganese ternary precursor is prepared by the preparation method as described in any one of claims 1 to 4, and is composed of nickel-cobalt-manganese hydroxide, has a granular appearance, and the particle body is composed of stacked sheets grown along the c-axis.

6. The nickel-cobalt-manganese ternary precursor according to claim 5, characterized in that: The average particle size of the particles is 2.5-3.2 μm, and the tap density is 1.75-2.05 g / cm 3 .

7. A lithium ion battery, characterized in that: It contains a single crystal positive electrode material prepared from the nickel-cobalt-manganese ternary precursor as claimed in claim 5.